Suicide Risk Assessment Team-Based Learning (TBL) Module - Matthew Goldenberg; Kenan Penaskovic (Association of American Medical Colleges, 2012)
Abstract This resource is a Team-Based Learning Module on suicide risk assessment. Learning to assess a patient's risk for suicide or self-harm is a primary objective of undergraduate medical education. The Association of Directors of Medical Student Education in Psychiatry (ADMSEP) has set forth a series of core learning objectives related to suicide assessment including (1) identifying and discussing risk factors for suicide across the lifespan, (2) conducting diagnostic and risk assessments of a patient with suicidal thoughts or behavior and making recommendations for further evaluation and management, (3) analyzing risk factors and making recommendations for psychiatric hospitalization versus an ambulatory disposition in the management of designated patients. This module addresses all three objectives in a team-based learning format which encourages student pre-class preparation, active participation and collaboration. In accordance with the approved TBL method, this module consists of a pre-class reading assignment, individual and group readiness assurance tests and an application exercise. The application exercise consists of two parts, both presented in the form of clinical cases about which students have to make specific decisions, and teams must report their decisions simultaneously. We have used this module during the third-year clinical clerkship for over a year at our institution as a part of our new team-based learning (TBL) curriculum. Feedback from students regarding the TBL curriculum has been generally positive on anonymous, end-of-clerkship evaluations. NBME scores increased by a statistically significant amount over prior year's scores and were significantly higher at sites that utilized the TBL curriculum when compared with those that did not.